Pricing the ecosystem and taxing ecosystem services: A general equilibrium approach - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2007)
In an integrated dynamic general equilibrium model of the economy and the ecosystem humans and wildlife species compete for land and prey biomass. We introduce a competitive allocation mechanism in both submodels such that economic prices and ecosystem prices guide the allocation in the economy and in the ecosystem, respectively. We distinguish the scenarios of an open accessible habitat and a privately owned habitat. In both scenarios efficiency requires different corrective taxes/subsidies to internalize consumption services externalities. In the case of an open access habitat additional sources of inefficiency are the divergence of prices for biomass and land in both subsystems. Finally, we determine values of all components of the ecosystem in an efficient steady state with special emphasis on the role and the interplay of ecosystem and economic prices.
Keywords: H21; Q28; 330; land; biomass; ecosystem services; Umwelt; Bodennutzung; Internalisierung externer Effekte; Erneuerbare Ressourcen; Umweltabgabe; Allgemeines Gleichgewicht; Theorie